Pengaruh Penyediaan Jalur Khusus Sepeda Diatas Badan Jalan (Sky Road) Terhadap Kinerja Jalan Di Kota Malang (Studi Kasus Jalan Borobudur – Soekarno Hatta) P2M Politeknik Negeri Malang Tahun 2018 - marjono marjono (Prokons: Jurnal Teknik Sipil, 2019)
Abstract :One of the problems felt by the people of Malang City is the problem of congestion and traffic system irregularities. Borbudur -Soekarno Hatta road, including roads that experience traffic problems, namely frequent traffic jams, especially at the time of departure or return to school, and hours of departure and return to work, this is because the road is the road access to the education area , trade and one of the access roads that lead to the center of Malang City. If this is not done immediately, the traffic problems will increase. A possible alternative to overcome this problem is to reduce motorbike users entering the road, by diverting some motorbike users to non-motorized bikes (bicycles) primarily for purposes of educational facilities, by providing special lanes for bicycles, which above the road (Sky Road). From the results of the analysis it can be seen that by providing a Bicycle Special Path above the Road Body (Sky Road), it can reduce the value of degree of saturation (DS) and can increase the level of service from C to B. Estimated cost of the main Sky road structure Rp. 9. 236,308 000 ,, - (Nine Billion Two Hundred Thirty-Six Million Three Hundred Eight Thousand Rupiahs) Keywords: special bike lanes, sky road, road performance